The Influence of Human Resource Competence on Employee Performance at the Ministry of Public Works and Housing, Pompengan Jeneberang River Basin Center, Makassar - Fahrur Rijal; Siti Marhumi; Muhammad Akib (GoodWill, 2026)
This study examines the influence of human resource (HR) competence on employee performance at the Ministry of Public Works and Public Housing, Pompengan Jeneberang River Basin Center, Makassar. HR competence, encompassing knowledge, skills, and work attitudes, is considered a critical factor in enhancing organizational effectiveness, particularly in public sector institutions that demand high accountability and service quality. This research adopts a quantitative approach using a saturated sampling technique, involving all 34 employees as respondents. Data were collected through structured questionnaires and analyzed using simple linear regression, validity and reliability tests, classical assumption tests, and t-tests. The findings reveal that HR competence has a positive and significant effect on employee performance. The regression results show a coefficient of 0.408, indicating that improvements in competence lead to increased employee performance. Furthermore, the t-test results demonstrate a significance value of 0.000, which is lower than the 0.05 threshold, and a calculated t-value of 9.766 exceeding the t-table value, confirming the acceptance of the research hypothesis. These results highlight the importance of competency development in improving employee productivity, work quality, and organizational performance. The study contributes to human resource management literature by providing empirical evidence from a public sector context. Practically, the findings suggest that organizations should prioritize training and competency-based development programs to enhance employee performance and achieve institutional objectives effectively.